2021
DOI: 10.1016/j.mvr.2021.104224
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of endothelial dysfunction and outcomes in coronavirus disease 2019 (COVID-19) patients: A systematic review and meta-analysis

Abstract: Background Several studies have reported that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can directly infect endothelial cells, and endothelial dysfunction is often found in severe cases of coronavirus disease 2019 (COVID-19). To better understand the prognostic values of endothelial dysfunction in COVID-19-associated coagulopathy, we conducted a systematic review and meta-analysis to assess biomarkers of endothelial cells in patients with COVID-19. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 45 publications
(45 reference statements)
4
25
0
2
Order By: Relevance
“…Meta-analysis showed that higher plasma levels of vWF antigen, tissue-type plasminogen activator, plasminogen activator inhibitor-1 antigen and soluble thrombomodulin were associated with poor outcome. 41 In the liver, strong vWF staining in sinusoidal endothelial cells was associated with increased platelet adhesion. 42 Consistent with these observations, we found increased immunostaining for vWF in the microthrombi.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis showed that higher plasma levels of vWF antigen, tissue-type plasminogen activator, plasminogen activator inhibitor-1 antigen and soluble thrombomodulin were associated with poor outcome. 41 In the liver, strong vWF staining in sinusoidal endothelial cells was associated with increased platelet adhesion. 42 Consistent with these observations, we found increased immunostaining for vWF in the microthrombi.…”
Section: Discussionmentioning
confidence: 99%
“…Several biomarkers other than cytokines have been found altered in COVID-19, and are associated with diagnosis, prognosis and outcomes ( 7 ). Some of these biomarkers can be easily used to predict disease severity, hospitalization, intensive care unit (ICU) admission, and mortality, while others, like metabolomic and proteomic analysis, are still of purely investigational concern and difficult to translate into clinical practice, despite their prognostic potential ( 8 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In July 2021, Andrianto et al [ 62 ] conducted a literature search for observational studies that analysed the relationship between ED biomarkers and clinical outcomes in COVID-19 patients. In a meta-analysis that included 1187 patients from 17 studies, VWF antigen, PAI-1, t-PA, sTM were predictors of worse outcome in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%